A pilot study examining skin cancer education in an underserved population at a free skin cancer screening - Herbert B. Castillo Valladares, MD; Alison K. Lee, MD, MHS; Shayan Cheraghlou, BA; Amanda Zhou, BS; Sarika Ramachandran, MD (Wolters Kluwer, 2021)
Background: Minority populations are increasingly diagnosed with skin cancer and often in later stages with more aggressive subtypes. Objective: We sought to pilot a study to evaluate the effectiveness of providing a skin cancer screening and education module to address potential barriers to dermatologic care for an underserved population in New Haven, Connecticut. Methods: At a free clinic, voluntary adults (n = 24) waiting for a skin cancer screening were recruited and consented to participate. Participants completed a 16-question survey prior to the total body-skin examination and the educational module, as well as a survey after the examination. Results: Most participants were uninsured (79%) and Hispanic (71%). Pre- and postintervention surveys indicated significant increases in knowledge, risk awareness, and confidence for self-screening. Conclusion: This study establishes an effective public health education intervention to promote the prevention of skin cancer. A multicenter study with a larger sample size and longer follow-up period to assess knowledge retention could further address limitations in this initial pilot study.